PERSUASION BY J. AUSTEN AS A SEMANTIC SEGMENT FULFILLING FUNCTION OF LIMITED CLASS PRIDE - Chorieva Mukhlisa Jumamurodovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article “Persuasion” by Jane Austen is analyzed semantically, especially the concept of pride and its meaning throughout the work. Different meanings and features of the concept of pride are learned in terms of characters and context in the work of Jane Austen.